2022
DOI: 10.1111/jocd.14791
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ablative fractional carbon dioxide laser combined with autologous platelet‐rich plasma versus ablative fractional carbon dioxide laser and placebo in the treatment of striae gravidarum: A randomized clinical trial

Abstract: Background: Striae gravidarum (SG) is a connective tissue disorder seen commonly in primigravidas. It is associated with impairment in the quality of life.Objective: To determine the efficacy of ablative fractional carbon dioxide (CO 2 ) laser combined with autologous platelet-rich plasma (PRP) versus ablative fractional CO 2 laser and placebo in the treatment of SG.Study design: Randomized, double-blinded, and placebo-controlled trial. Methodology:The study was conducted in 16 patients with SG. The assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…While combination therapy is generally considered the best approach to SD, contradictory results have been observed in different studies involving various modalities [39][40][41]. A review study conducted in 2021 to evaluate the effectiveness of the PRP method in treating striae distensae revealed that the published studies in this field did not provide strong evidence of the effectiveness of PRP [42].…”
Section: Discussionmentioning
confidence: 99%
“…While combination therapy is generally considered the best approach to SD, contradictory results have been observed in different studies involving various modalities [39][40][41]. A review study conducted in 2021 to evaluate the effectiveness of the PRP method in treating striae distensae revealed that the published studies in this field did not provide strong evidence of the effectiveness of PRP [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, Preclaro and colleagues [ 52 ] also studied the synergistic effect of a fractional CO 2 laser with PRP, albeit in striae gravidarum (S.G.), a connective-tissue dysfunction commonly observed in primigravidae. They evaluated 16 patients with S.G. treated with a fractional CO 2 laser followed by PRP on one side of the abdomen and with a fractional CO 2 laser followed by normal saline on the other.…”
Section: Striaementioning
confidence: 99%
“… 47 In the last two years, it has been shown that FrCO 2 combined with PRP is also an effective treatment for SD and is superior to FrCO 2 alone or PDL combined with PRP. 48 , 49 Some of the clinical trials of combined treatment modalities have been tabulated in Table 2 .…”
Section: Combination Therapiesmentioning
confidence: 99%